2020
DOI: 10.12784/nzcomjnl56.2020.3.17-25
|View full text |Cite
|
Sign up to set email alerts
|

Rural midwifery practice in Aotearoa/New Zealand: Strengths, vulnerabilities, opportunities and challenges

Abstract: Background: The sustainability of rural maternity services is threatened by underfunding, insufficient resourcing and challenges with recruitment and retention of midwives. Aims: The broader aim of this study was to gain knowledge to inform the optimisation of equitable and sustainable maternity care for rural communities within New Zealand and Scotland, through eliciting the views of rural midwives about their working conditions and practice. This article focuses on the New Zealand midwives’ responses. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…A notable exception to this in our findings was the rural midwifery context, in which rural midwives tend to mentor and be mentored by other rural midwives, and conflict at the rural/urban interface remains a key issue despite the support provided by the rural midwife mentors around this. This is supported by the Aotearoa-based literature, which describes rural midwives' experiences of negative judgement and unfair treatment at the urban/rural interface due to a lack of understanding of the realities of rural practice, which can be disempowering and impact on job satisfaction (Crowther, 2016;Crowther et al, 2018;Daellenbach et al, 2020). Daellenbach et al (2020) found that rural midwives identified mentoring as a strategy for supporting them with interface challenges.…”
Section: Strengthening the Professionmentioning
confidence: 85%
See 1 more Smart Citation
“…A notable exception to this in our findings was the rural midwifery context, in which rural midwives tend to mentor and be mentored by other rural midwives, and conflict at the rural/urban interface remains a key issue despite the support provided by the rural midwife mentors around this. This is supported by the Aotearoa-based literature, which describes rural midwives' experiences of negative judgement and unfair treatment at the urban/rural interface due to a lack of understanding of the realities of rural practice, which can be disempowering and impact on job satisfaction (Crowther, 2016;Crowther et al, 2018;Daellenbach et al, 2020). Daellenbach et al (2020) found that rural midwives identified mentoring as a strategy for supporting them with interface challenges.…”
Section: Strengthening the Professionmentioning
confidence: 85%
“…This programme provides peer mentoring support to rural and remote rural midwives facing the unique professional and personal demands of providing LMC midwifery care in isolated and sparsely populated areas (Crowther, 2016). Having a rural mentor has been identified by rural midwives as a key strategy for sustaining them in rural practice (Daellenbach et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, midwives identified the allocated caseload of 38 women, in addition to providing postnatal home care to women returning after birthing in metropolitan services to be a significant challenge. Concern around regional/rural caseload is not new, with studies asserting that the caseload contract system has been designed for urban‐based midwives and that it does not work as well for rural maternity services 23,24 . In a study which explored midwives working in a caseload model in rural Victoria, 22 the on‐call element of caseload interrupted midwives' personal lives and was one of the most difficult factors.…”
Section: Discussionmentioning
confidence: 99%
“…Concern around regional/rural caseload is not new, with studies asserting that the caseload contract system has been designed for urban-based midwives and that it does not work as well for rural maternity services. 23,24 In a study which explored midwives working in a caseload model in rural Victoria, 22 the on-call element of caseload interrupted midwives' personal lives and was one of the most difficult factors. Similar to this study, being called in for a birth would necessitate reorganisation of other appointments, impacting not only the women but other care providers as well.…”
Section: Challenges Implementing a Rural Mmocmentioning
confidence: 99%
“…2021 NZ podiatry workforce data indicates approximately 70% of podiatrists work in major or large urban centres as classified by Statistics New Zealand functional rural-urban classification (Urban Rural Experimental Profile 2004; UREP) [2]. However, defining the NZ rural/urban population attributes for research purposes is difficult as there is no consistent agreed definition of rurality [3]. The current UREP classification of urban/rural attributes based upon population size has been criticised as the population defined as "rural" differs from that which actually receives rural health care [4].…”
Section: Introductionmentioning
confidence: 99%